Dynamic Analysis of Bajaj Pulsar 150cc Connecting Rod Using ANSYS 14.0 - Kumar, Amit; Bhingole P.P.; Kumar, Dinesh (Asian Journal of Engineering and Applied Technology, 2014)
Connecting rod is an important part of i.c. Engine which form link between piston and crankshaft to convert linear reciprocating motion of the piston to the rotary motion of the crankshaft. Till now, vast research is going on in the field of metallurgy and resulted in large number of newly developed materials are available to select materials for particular applications. Focusing on this issue, in this study the connecting rod modulate and simulated for the dynamic analysis by using catia software for modelling-design of connecting rod and ansys 14.0 for dynamic analysis. Using available high strengthen alloy is used for the connecting rod of bajaj pulsar 150cc for the weight reduction to reduce moment of inertia. Dynamic analysis is carried out for determine the von mises stress, strain, and total deformation is calculated under loading conditions of compression and tension at crank end and pin end of connecting rod.